2014
DOI: 10.1164/rccm.201307-1229oc
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Need for Palliative Care Consultation across United States Intensive Care Units Using a Trigger-based Model

Abstract: Approximately one in seven ICU admissions met triggers for palliative care consultation using a single set of triggers, with an upper estimate of one in five patients using multiple sets of triggers; these estimates were consistent across different types of ICUs and individual units. These results may inform staffing requirements for providers to ensure delivery of specialized palliative care to ICU patients nationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
135
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 51 publications
0
135
0
3
Order By: Relevance
“…3,4,8,46,47 Prior work emphasizes the importance of care provision by clinicians with expertise in palliative care, 47 yet palliative care consultation services cannot see all seriously ill ICU patients. 48 For example, only 36% of patients discussed on our rounds received a palliative care service consultation. We provided bedside nurses with the core skills that palliative care consultants use to navigate discussions of prognosis and goals of care and coached them as they incorporated these skills in practice.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,8,46,47 Prior work emphasizes the importance of care provision by clinicians with expertise in palliative care, 47 yet palliative care consultation services cannot see all seriously ill ICU patients. 48 For example, only 36% of patients discussed on our rounds received a palliative care service consultation. We provided bedside nurses with the core skills that palliative care consultants use to navigate discussions of prognosis and goals of care and coached them as they incorporated these skills in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the "right" penetration level has not been determined, 3.4 percent is likely below the need for consultation among hospital patients. One recent study estimated that 13.8 percent of intensive care unit admissions met criteria for palliative care consultation, 23 and a study in a large cancer center estimated that one-third of hospitalized cancer patients should receive a palliative care consultation. 24 In addition, we found that one-third of palliative care programs did not have recommended coverage-personnel available on site during weekday business hours and by telephone at all times.…”
Section: Discussionmentioning
confidence: 99%
“…These can be administered by multiple types of hospital personnel, streamline the referral process, and reduce the odds that patients' needs are missed. 23,24,34 Managers should ensure that their palliative care programs collaborate with other related hospital programs such as advance care planning, case management, and pain services.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the PC needs of patients with critical disease in ICU and their families, there must be personnel specialised in the field of PC, with sufficient knowledge and skills. In this approach, the ICU clinicians request PC consultations from PC specialists, but it has been reported that the requirement of PC consultation by ICU clinicians or acceptance of the need could take more time [37]. It could be useful for the PC consultants to participate in the ICU daily patient visits in respect of showing regular collaboration and benefits.…”
Section: Consultative Modelmentioning
confidence: 99%
“…According to this Project, the situations requiring PC consultation are given under five headings [27,37]. …”
Section: Consultative Modelmentioning
confidence: 99%